PROBLEMATIKA SANTRI DALAM MENGHAFAL AL-QUR’AN TINJAUAN PSIKOLOGI BELAJAR DI PONDOK PESANTREN DARUL FALAH III CUKIR JOMBANG - Habibillah Habibillah; Syamsuddin Syamsuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Problematics refers to problems that have not been resolved. Memorizing the Qur'an means reading it repeatedly and continuously orally so that memories are created that are embedded in the heart and mind, so that they can be applied in everyday life. Learning psychology is a field of study that focuses on understanding and analyzing principles related to human behavior during the learning process. The focus of the problem in this study is (1).How the problems of memorizing the Qur'an at the Darul Falah III Cukir Jombang Islamic Boarding School, (2). How the problems of students in memorizing the Qur'an Review of the psychology of learning at the Darul Falah III Cukir Jombang Islamic Boarding School, (3). What are the factors that influence memorizing the Qur'an at the Darul Falah III Cukir Jombang Islamic Boarding School. To obtain answers to questions from the research focus, the researcher applied a qualitative field research method with a case study type and data collection techniques including observation, interviews and documentation. The results of the study (1) Problems in Memorizing the Qur'an of students in memorizing the Qur'an are divided into two, namely Internal Factors including demotivation, boredom, laziness, weak memory, and difficulty in managing time. External Factors include difficulty memorizing long letters (As-Sab'ut Tiwal), concentration disorders due to the use of mobile phones, lack of mastery of tajwid science, and the influence of an unfavorable environment. (2) Problems in memorizing the Qur'an when viewed from the perspective of learning psychology are in accordance with the Behaviorist Theory in the form of external pressure (such as parental demands) without positive encouragement causing stress and decreased motivation. Cognitive Theory in the form of physical fatigue that increases cognitive load so that it inhibits the storage of information in working memory. Emotional disorders (anxiety, not in the mood) in accordance with the Humanistic Theory, namely emotional instability and an uncomfortable environment inhibit self-actualization. (3) Factors that influence students' memorization in the memorization process include the Murajaah System, the role of teachers, various memorization methods that are adjusted to the needs of students. A conducive Islamic boarding school environment and peer support.